2018
DOI: 10.1007/s13187-018-1321-0
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Mammography Screening Educational Interventions for Hispanic Women in the United States

Abstract: In the United States (U.S.), Hispanics experience breast cancer disparities. Breast cancer is the leading cause of cancer-related death among Hispanic women, and Hispanic women receive mammography screening at lower rates than some other ethnic groups. This low rate of screening mammography is associated with increased risk for possible late-stage diagnosis and lower survival rates. Educational interventions could play a role in increasing screening mammography rates among Hispanic women. This systematic revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 35 publications
1
44
0
1
Order By: Relevance
“…Educational interventions about health literacy have been developed to improve health-related behavior, including cancer screening (Van den Broucke et al, 2014; Crowley et al, 2013). One review has suggested that such interventions help mediate the impact of barriers to undergoing cancer screening, such as low health literacy (Luque et al, 2018). One Japanese report found that health education designed to impart knowledge and interpersonal skills may improve health literacy beyond functional health literacy (Ishikawa et al, 2018); however, in Japan, there are few educational opportunities to support health management with respect to health literacy.…”
Section: Discussionmentioning
confidence: 99%
“…Educational interventions about health literacy have been developed to improve health-related behavior, including cancer screening (Van den Broucke et al, 2014; Crowley et al, 2013). One review has suggested that such interventions help mediate the impact of barriers to undergoing cancer screening, such as low health literacy (Luque et al, 2018). One Japanese report found that health education designed to impart knowledge and interpersonal skills may improve health literacy beyond functional health literacy (Ishikawa et al, 2018); however, in Japan, there are few educational opportunities to support health management with respect to health literacy.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, rates of cancer screening for migrants to Australia are slightly lower than the Australian born population [14][15][16]. There is also some evidence of a socioeconomic gradient in screening [17][18][19], and while this is not conclusive [20], studies have identified patterns of more advanced disease at diagnosis among diverse cultural or lower socioeconomic groups [21][22][23]. It is therefore important to target strategies to improve uptake of screening among these at-risk groups.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the category of “where care is provided and changes in the healthcare environment,” several reviews included interventions that focused on improving access to healthcare services by connecting healthcare professionals to work or educational institutions, or directly to the homes of vulnerable populations with geographic difficulties or who had been displaced, to provide access health care [ 43 45 ]. In this context, subjects such as healthy eating in the school environment in low-income countries [ 36 ], assessment and rapid testing for the human immunodeficiency virus in street dwellers or disadvantaged women [ 19 , 46 ], medical visits for detection of colorectal, breast and cervical cancer [ 47 51 ], and informed advocacy measures in the community to promote cardiovascular disease protective factors [ 27 , 52 ] had positive effects when implemented in places where there are concentrations of disadvantaged groups, thus improving access to health care.…”
Section: Resultsmentioning
confidence: 99%